DETERMINANTS OF CHOOSING A CAREER AS A PUBLIC ACCOUNTANT - Safitri, Yolanda Aprilia; Rahayu , Ruci Arizanda (ANTIS PUBLISHER, 2024)
General Background: Career decisions are influenced by various factors, particularly when choosing a public accounting profession. Specific Background: Despite the growing need for public accountants, there is limited research on the determinants that shape students’ career choices in this field. Knowledge Gap: Few studies examine how factors like financial rewards, work environment, market considerations, social values, and professional training affect the interest in pursuing public accounting careers. Aims: This study seeks to identify and analyze these factors among accounting students at Muhammadiyah University of Sidoarjo. Results: The research reveals that financial rewards, work environment, and social values significantly influence students' interest in becoming public accountants, while market considerations and professional training do not show significant effects. Novelty: The study offers a comprehensive analysis of the decision-making process regarding career choices in public accounting, highlighting the underestimated role of professional training and market considerations, which had been previously assumed to be critical factors. Implications: These findings suggest that universities and organizations need to focus on enhancing the perceived benefits of the work environment, financial rewards, and social values when promoting public accounting as a viable career choice. The study contributes valuable insights for educators and policy-makers in understanding the motivators for students pursuing careers in public accounting.